2021
DOI: 10.1136/bmjopen-2021-049389
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effective mask use by the public in two countries: an observational study

Abstract: ObjectivesDuring the COVID-19 pandemic wearing a mask in public has been recommended in some settings and mandated in others. How often this advice is followed, how well, and whether it inadvertently leads to more disease transmission opportunities due to a combination of improper use and physical distancing lapses is unknown.DesignCross-sectional observational study performed in June–August 2020.SettingEleven outdoor and indoor public settings (some with mandated mask use, some without) each in Toronto, Ontar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The four observational studies found either a positive or a neutral relationship between face covering use or face covering policy and physical distancing. Three observational studies found no significant relationship between face covering use (self) or face covering policy and physical distancing [ 37 : two studies], [ 39 ], while the fourth observational study found that physical distancing was greater in those who wore face coverings, and also that it was greater when a face covering mandate was implemented [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four observational studies found either a positive or a neutral relationship between face covering use or face covering policy and physical distancing. Three observational studies found no significant relationship between face covering use (self) or face covering policy and physical distancing [ 37 : two studies], [ 39 ], while the fourth observational study found that physical distancing was greater in those who wore face coverings, and also that it was greater when a face covering mandate was implemented [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were also 17 studies in which, although the authors did not assess impact of face covering policy, they did provide information on the real-world policy implemented during the time of study; that is whether face covering use was mandatory, voluntary or whether the policy was varied (i.e., that for some of the duration of the study it was mandatory, and for some of the time it was voluntary). Of the 17, thirteen studies focused on physical distancing (five carried out in a mandatory face covering context, six in a voluntary face covering context, and two in contexts where the policy varied between the two) and results across studies were mixed in all three contexts [ 28 : two studies, 29 , 31 : two studies, 33 , 35 , 37 , 40 , 41 , 44 46 ]. Two focused on mobility, and in both cases face covering use was voluntary but a positive association was found in one [ 46 ] and a negative association in the other [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken collectively, these individual harms can significantly hamper health care systems’ ability to provide basic care for all individuals in need when many individuals get infected in the same period, as it typically happens during pandemic waves (35 36 on the lack of sufficient intensive care units experienced across countries during early pandemic waves;37 38 on the considerable increases in backlogs and waiting times accumulated in the NHS through the pandemic). In this context, MWM can effectively reduce the harms deriving from individuals’ failure to wear masks in indoor settings where physical distancing is infeasible by substantially increasing and sustaining high community mask wearing rates 4 39 40. For as demonstrated by a wide range of experimental and observational studies, community mask wearing can reduce COVID-19 transmission in proportion to mask effectiveness and adoption rates even after controlling for other mitigation measures 41–49.…”
Section: A Case For Mwmmentioning
confidence: 99%
“…There are at least three reasons to doubt that MWR provide a more effective, just and fair way to tackle the ongoing COVID-19 pandemic than MWM. First, MWM can substantially increase community mask wearing rates compared with MWR 4 39 40. Moreover, MWM can effectively sustain high community mask wearing rates by leading individuals to regard mask wearing as what most people do (and ought to do) to protect themselves and others 108 109.…”
Section: Objections and Repliesmentioning
confidence: 99%
“…The four observational studies found either a positive or a neutral relationship between face covering use or face covering policy and physical distancing. Three observational studies found no significant relationship between face covering use (self) or face covering policy and physical distancing (33: two studies), (35), while the fourth observational study found that physical distancing was greater in those who wore face coverings, and also that it was greater when a face covering mandate was implemented (36). Four of the six correlational studies found that as self-reported face covering use (self or other) increased, so did self-reported physical distancing (37)(38)(39)(40).…”
Section: Physical Distancing (See Table 2a In S3 Appendix For Full De...mentioning
confidence: 99%